2019
DOI: 10.3889/oamjms.2019.647
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyle Characteristics in Non-Alcoholic Fatty Liver Disease in the PERSIAN Guilan Cohort Study

Abstract: BACKGROUND: Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common cause of chronic liver disease worldwide. Since the effect and safety of pharmacotherapy for NAFLD are unknown, the proper management of lifestyle is crucial. AIM: The present study was conducted to determine the status of food, Physical Activity (PA), and sleep in patients with and without NAFLD. METHODS: In this analytical- cross-sectional study, 630 clients with 36-60 years old who referred to the PERSIAN Guilan cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In fact, a previous study reported that the prevalence of eating fast in patients with diabetes was 61.5% [30], which was higher than that in healthy subjects [16,18]. In addition, in this study, eating fast was associated with NAFLD in men, which is the same as previous studies [19][20][21]. On the other hand, eating speed was not association with the presence of NAFLD in women.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, a previous study reported that the prevalence of eating fast in patients with diabetes was 61.5% [30], which was higher than that in healthy subjects [16,18]. In addition, in this study, eating fast was associated with NAFLD in men, which is the same as previous studies [19][20][21]. On the other hand, eating speed was not association with the presence of NAFLD in women.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, it has been shown that eating fast is associated with metabolic syndrome [10,17] and T2DM [16,18]. Furthermore, several studies have also revealed that eating fast is associated with NAFLD in the general population [19][20][21]. However, the association between eating speed and NAFLD in patients with T2DM has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise can reduce the formation of free fatty acids, inhibit insulin resistance, reduce the risk factors for MAFLD, and has even been shown to reverse the condition [26] . Our study also found that children with fatty liver appeared to engage in less exercise, which is consistent with the results of the study of adults conducted by Mansour-Ghanaei et al However, we did not nd a relationship between exercise intensity and fatty liver disease [27] . It has been reported that aerobic exercise and resistance exercise can reduce steatosis of MAFLD; people with poor cardiopulmonary function are more suited to resistance exercise [28] .…”
Section: Discussionsupporting
confidence: 93%
“…For the remaining 66 articles, 51 studies were further excluded owing to a lack of data on RRs, HRs, ORs, and 95% CIs ( n = 7), irrelevant results ( n = 20), and exposure factors ( n = 24). Finally, a total of 15 studies (two cohort studies, six case–control studies, and seven cross-sectional studies) 26–40 met the criteria, involving 65 149 participants (including 19 670 cases with NAFLD). Table 1 summarizes the study characteristics.…”
Section: Resultsmentioning
confidence: 99%